Bone Perspectives in Functional Hypothalamic Amenorrhoea: An Update and Future Avenues - Behary, Preeshila; Comninos, Alexander N. (Frontiers in Endocrinology, 2022)
One of the most important and potentially long-lasting detrimental consequences of Functional Hypothalamic Amenorrhoea (FHA) is on skeletal homeostasis. Beyond oestrogen deficiency, FHA is associated with a cascade of additional neuro-endocrine and metabolic alterations, some adaptive, but which combine to disrupt skeletal homeostasis. Ultimately, this leads to a two-fold increased risk of fractures in women with FHA compared to healthy eumenorrhoeic women. Although the cornerstone of management of FHA-related bone loss remains recovery of menses via restoration of metabolic/psychological balance, there is rapidly developing evidence for hormonal manipulations (with a particular emphasis on route of administration) and other pharmacological treatments that can protect or improve skeletal homeostasis in FHA. In this mini-review, we provide an update on the pathophysiology, clinical management and future avenues in the field from a bone perspective.